Energy Market Liberalisation in Greece: Structures, Policy and Prospects - Vlados, Charis; Chatzinikolaou, Dimos; Kapaltzoglou, Foteini (International Journal of Energy Economics and Policy, 2021)
The ongoing regulatory transformation towards a single European electricity market started several years ago. The rationale of this transformation is that the liberalisation of monopolistic energy structures should lead to the building of sustainable and flexible energy ecosystems, through an energy policy that sets goals in line with the requirements of our epoch, such as sustainable development, energy security, and the promotion of renewable energy sources. In this context, the liberalisation of the electricity market in Greece is explored, which is a complicated case in terms of development as it has only recently begun to exit from a long-term socio-economic crisis and strict adjustment programs. The concepts of energy market liberalisation, energy ecosystems, and energy policy are presented and compared to the main directions of the EU institutional environment and the evolution of the political and institutional framework of Greece. In Greece, an attempt has been made in recent years to liberalise the electricity market, which is hindered for a long time by socio-economic forces favoured by the monopolistic system of the market. This liberalisation process is also an opportunity for the country to move towards enhancing the structures that can lead to faster and more sustainable development and to maintain the pace of “coupling” with the most developed energy economies of Europe. Keywords: Energy market liberalisation, Electricity market liberalisation, Energy business ecosystem, Energy policy, EU energy packages, Greek energy system JEL Classifications: Q40, Q43, Q49 DOI: https://doi.org/10.32479/ijeep.10804